PERANCANGAN SISTEM INFORMASI DATA KUNJUNGAN NASABAH BANK MUAMALAT BERBASIS WEB - Qori Azmi Ayasy Siagian Siagian; Mukamal Bil Syahbana Angkat (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Technological developments are increasingly rapid with all the conveniences in assisting human activities both personally and in groups. From these activities get an important information stored. The customer transaction process still applies a manual system for recording all customer transactions using the cooperative ledger. This causes bank officers to find it difficult and convoluted in managing data, which is increasing day by day. The solution to the problems that occur at Bank Muamalat Medan is the application of information technology by installing an information or relevance system that allows officers to handle customer data. This research was built using PHP programming by operating PHP and MySQL as the database. The research results can be used in the process of controlling customer data at Bank Muamalat so that it can speed up the process of recording customer data.